In vitro antibacterial activity of Myrica javanica leaf extract against Staphylococcus aureus and Propionibacterium acnes. - Varda Arianti; Yeni Marsela; Devi Maulina; Gaine Marvelous; Pra Panca Bayu Chandra (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Based on the Myrica genus, Myrica esculenta contains secondary metabolites such as flavonoids, steroids, tannins, alkaloids, and saponins, that have the potential to act as antibacterial agents. This study aims to evaluate the antibacterial effectiveness of Myrica javanica extract against Staphylococcus aureus and Propionibacterium acnes in vitro. Extraction was performed using the maceration method with 96% ethanol, followed by antibacterial activity testing using the disk diffusion method at five extract concentrations (20%, 40%, 60%, 80%, 100%) with positive control (Clindamycin) and negative control (DMSO). The results showed an increase in the maximum inhibition zone against the bacteria Staphylococcus aureus and Propionibacterium acnes measuring 14,04 ± 0,50 mm and 12,3 ± 0,64 mm respectively at concentration of 100%. In conclusion, the extract of Myrica javanica shows potential antibacterial activity against both test bacteria.